Safety and Efficacy of an On-Site Intensive Treatment Protocol for Mild and Moderate Sympathomimetic Toxicity at Australian Music Festivals. Issue 1 (6th February 2020) - Douglas, Ned; Carew, James; Johnson, Damian; Green, Madeline; Wilson, Nicholas; Donovan, Jake; Mulherin, Tim; Holbery-Morgan, Lachlan; Bourke, Elyssia; Smith, Erin
Abstract: Introduction: Serotonin and sympathomimetic toxicity (SST) after ingestion of amphetamine-based drugs can lead to severe morbidity and death. There have been evaluations of the safety and efficacy of on-site treatment protocols for SST at music festivals. Problem: The study aimed to examine the safety and efficacy of treating patients with SST on-site at a music festival using a protocol adapted from hospital-based treatment of SST. Methods: The study is an audit of presentations with SST over a one-year period. The primary outcome was need for ambulance transport to hospital. The threshold for safety was prospectively defined as less than 10% of patients requiring ambulance transport to hospital. The protocol suggested patients be treated with a combination of benzodiazepines; cold intravenous (IV) fluid; specific therapies (cyproheptadine, chlorpromazine, and clonidine); rapid sequence intubation; and cooling with ice, misted water, and convection techniques. Results: One patient of 13 (7.7%) patients with mild or moderate SST required ambulance transport to hospital. Two of seven further patients with severe SST required transport to hospital. Conclusions: On-site treatment may be a safe, efficacious, and efficient alternative to urgent transport to hospital for patients with mild and moderate SST. The keys to success of the protocol tested included inclusive and clear education of staff at all levels of the organization, robust referral pathways to senior clinical staff, and the rapid delivery of therapies aimed at rapidly lowering body temperature. Further collaborative research is required to define the optimal approach to patients with SST at music festivals.